Movement ecology of large herbivores in African savannas: current knowledge and gaps. (7th April 2020) - Owen‐Smith, Norman; Hopcraft, Grant; Morrison, Thomas; Chamaillé‐Jammes, Simon; Hetem, Robyn; Bennitt, Emily; Van Langevelde, Frank
Abstract: Nearly 90% of the world's large herbivore diversity occurs in Africa, yet there is a striking dearth of information on the movement ecology of these organisms compared to herbivores living in higher latitude ecosystems. The environmental context for movements of large herbivores in African savanna ecosystems has several distinguishing features. African large herbivores move in landscapes with high spatiotemporal variability, low predictability, seasonal restrictions in surface water as well as food resources, and exposure to a diverse assemblage of competitors, predators, and pathogens. These features influence mobility, diel activity routines, home‐range fidelity, and exposure to predation. We review the knowledge that has been gained about the movements of African herbivores from Global Positioning System (GPS) telemetry and identify important gaps in knowledge that exist. Topics addressed include seasonal movement patterns, daily activity schedules, space utilisation, water dependency, responses to risks of predation, pathogen transmission, social affiliations, and local population density determination. While the growing number of GPS telemetry studies has addressed a wide range of topics in Africa, they remain fragmentary in terms of places and species represented. Most research has been focussed on three species, and practices for data sharing and analysis should be improved. African landscapes are changing perhaps faster than any other region on Earth, with rapidly expanding human populations, massive infrastructure development projects, and changes in climatic regimes. There is a crucial need to establish relationships between herbivore movements and their changing environments, especially in Africa where most of the world's large herbivore diversity resides. Abstract : GPS telemetry has opened opportunities to track the detailed movements of animals over periods of a year or longer and infer the mechanisms generating the data. Africa's large herbivores move through especially complex landscapes with seasonal variation in water resources as well as food availability and day–night contrasts in the risk of predation as well as temperature conditions. In response, some animals migrate between seasonally distinct home ranges over varying distances and exhibit strong daily rhythms in activities. Movement patterns affect how diseases are transmitted and underlie how populations are dispersed. Further research needs to encompass a wider range of species. Crucially, studies should address how movements are being affected by environmental change and human infrastructure, threatening population viability. The image depicts the movement track of a single migratory wildebeest over one full year in the Serengeti ecosystem, distinguishing a circuit to the west in the early wet season (green) followed by residence on the south‐eastern plains later in the wet season (blue) and thereafter migration northwards into Kenya during the dry season (grey).